Determining shoal membership: A comparison between momentary and trajectory-based methods - Quera, Vicenç; Beltran, Francesc S.; Dolado, Ruth (Behavioural brain research, 2011)
► Miller and Gerlai proposed two methods for determining shoal membership in Danio rerio. ► They used momentary and post hoc analysis of inter-individual distances. ► We propose an alternative method based on momentary nearest neighbor distances. ► We compare the three methods using agent-based simulation. ► Our method is simpler than Miller and Gerlai's post hoc method but tends to yield similar results. Miller and Gerlai proposed two methods for determining shoal membership in Danio rerio, one based on momentary mean inter-individual distances and the other on post hoc analysis of the trajectories of nearest-neighbor distances. We propose a method based on momentary nearest-neighbor distances and compare the three methods using simulation. In general, our method yielded results that were more similar to their second method than their first one, and is computationally simpler.